The third culture. - Stewart, Ian (New Statesman)
The article explores the importance of mathematics in society and culture. The funding of mathematics research in Great Britain and the U.S. as compared to other sciences is noted. Also discussed is the role of mathematics in the development of technologies such as global positioning systems, cancer research, and Internet search engines. The author argues that the public is not sufficiently informed of the contributions of mathematics to almost every facet of modern life.